2019
DOI: 10.1021/acssuschemeng.9b02858
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxygen Evolution in Acidic and Alkaline Media by a Multistimuli-Responsive Cobalt(II) Organogel

Abstract: Supramolecular gels and metallogels involving dynamic and reversible noncovalent interactions are touted as alternatives to gels based on polymeric materials for practical purposes and for an obvious edge in tailorability. A stimuliresponsive Co(II) containing a low-molecular-weight metalloorganogel (CoGel) has been synthesized on a nitrogen-rich triazole platform. CoGel shows autonomous self-healing ability owing to the presence of extensive hydrogen bonding between exocyclic amines of the triazole moiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 42 publications
(92 reference statements)
1
25
0
Order By: Relevance
“…Incorporation of metal components may enrich or modify gel morphologies, [8] and contribute to improve the optical, [9] electrochemical [10] and mechanical properties [11,12] . A variety of metal‐organic gels have been developed for various applications, such as selective adsorption, [11] biosensors, [13,14] and electrocatalysis [15] . Although the gels with various defined shapes or patterned structures are convenient for processing, delivery, and storage in large‐scale industrial production, [16–18] few metal‐organic gels with self‐supporting and moldable properties have been reported, [11,12,16,19,20] and metal‐organic gels with controllable shape, structure, and mechanical properties remains to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of metal components may enrich or modify gel morphologies, [8] and contribute to improve the optical, [9] electrochemical [10] and mechanical properties [11,12] . A variety of metal‐organic gels have been developed for various applications, such as selective adsorption, [11] biosensors, [13,14] and electrocatalysis [15] . Although the gels with various defined shapes or patterned structures are convenient for processing, delivery, and storage in large‐scale industrial production, [16–18] few metal‐organic gels with self‐supporting and moldable properties have been reported, [11,12,16,19,20] and metal‐organic gels with controllable shape, structure, and mechanical properties remains to be exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Other first-row transition metal compounds Ba [Co-POM] (40%); Cs [Co-POM] (40%) [218] 1.0 m H 2 SO 4 189 mV @1 mA cm −2 ; 306 mV @1 mA cm −2 97 mV dec −1 ; 98 mV dec −1 24 h@1.48 V RHE Gel-derived Co 3 O 4 [217] 0.5 m H 2 SO 4 441 mV @10 mA cm −2 171 mV dec −1 12 h@1 mA cm −2…”
Section: Mott-schottkymentioning
confidence: 99%
“…Similar to noble metal molecular complexes, transition‐metal‐ligand compounds have been also studied for water oxidation in acidic media, such as cobalt‐iron Prussian blue‐type thin films [ 216 ] and CoGel‐derived Co‐xerogel (xerogel1) with 3,5‐diamino‐1,2,4‐triazole (DAT) as the ligand. [ 217 ] Besides, Galan‐Mascaros and co‐workers demonstrated that barium cations incorporated cobalt‐containing polyoxometalates (Co‐POMs, [Co 9 (H 2 O) 6 (OH) 3 (HPO 4 ) 2 (PW 9 O 34 ) 3 ] −16 ) with 40% commercial carbon paste (CP) content, which is denoted as Ba[Co‐POM]/CP, can exhibit better activity at low current densities (189 mV at 1 mA cm –2 ) and competitive performance even at moderate current densities (361 mV at 10 mA cm −2 ). [ 218 ] In this regard, the counter‐cation Ba 2+ in the polyanionic property of POM with crystalline surface structure is favorable for the boosted OER under acidic condition.…”
Section: Electrocatalysts For Oer In Acidmentioning
confidence: 99%
“…So, the development of a highly stable trifunctional electrocatalyst active toward ORR, OER, as well as HER would be a blessing in disguise toward the commercialization process. Currently, few steps have been taken toward the realization of the trifunctional catalysts. Several protocols have been developed for the development of mono or bifunctional electrocatalysts such as metal-free and transition-metal impregnated nitrogen-doped carbon materials (MNCs), organic porous polymers, or soft materials like gels. These have been found to be cheap alternatives to the state-of-art precious metal-based catalyst (such as Pt/C, RuO 2 , IrO 2 ). Orderly distributed metal, N and C is crucial for efficient catalytic activity as well as stability.…”
Section: Introductionmentioning
confidence: 99%